Characterization of Construction and Demolition Waste in Order to Obtain Ca and Si Using a Citric Acid Treatment [Caracterización de Un Residuo de Construcción y Demolición Para la Obtención de Ca y Si Mediante Tratamiento Con Ácido Cítrico] - Navarro-Donoso, P; Vargas-Riquelme, C (Universidad Nacional de Colombia, 2016)
The paper analyses residual concrete (CW) degradation by organic acids and their potential use as nutrient source for degraded soils. The aims of the research were to carry out a chemical and mineralogical characterization of CW and to evaluate the dissolution of calcium and silicon from CW using citric acid in order to determine its potential use as a source of these elements for degraded soils. The chemical and mineralogical characterization made it possible to identify calcium and silicon as major elements associated with the concrete phases in the form of calcite, portlandite, hydrated calcium silicate, and hydrated calcium aluminosilicates. Calcium and silicon extraction was studied through a chemical and mineralogical analysis of CW (smaller than 4 mm), which was submerged in a citric acid solution for two days at 28°C and 110 rpm under controlled and uncontrolled pH conditions. Based on the concentration of calcium and silicon in solution, it was possible to conclude that after acidulation, this waste can be used as a source of nutrients for soils degraded by human use. © The author; licensee Universidad Nacional de Colombia.
Keywords: Construction and demolition waste (CDW); Dissolution and organic acid